A Palestinian State in Two Years : Institutions for Economic Revival - World Bank (Washington, DC, 2017)
On August 25, 2009, the 13th Government of the Palestinian Authority (PA) presented a program entitled "Palestine: ending the occupation, establishing the state" (hereafter referred to as the program) outlining several national goals, including the achievement of 'economic independence and national prosperity'. The program accords high priority to the development of the public institutions of the PA in order to achieve the stated national goals. It acknowledges that maintaining an efficient and effective public sector that provides citizens with high quality services and value for money is a constant challenge. No amount of well-functioning institutions, will, however, lead to economic growth in the absence of access to markets, whether within the West Bank and Gaza, in Israel, or in the rest of the world. In this regard, the recent developments in easing of movement and access restrictions by the Government of Israel (GoI) represent a welcome first step. The GoI has taken steps to ease movement restrictions in the West Bank and to allow greater access to West Bank markets for Arab citizens of Israel. In the first half of 2009, the political stalemate in Gaza continued and the economy stagnated. The West Bank economy is showing signs of new growth, so that it is possible that for the first time in years, West Bank and Gaza (WB&G) may have positive per capita Gross Domestic Product (GDP) growth in 2009.